Substrate masking ability of bilayer and monolithic ceramics used for complete crowns and the effect of association with an opaque resin-based luting agent. Issue 3 (July 2019) - Bacchi, Atais; Boccardi, Samara; Alessandretti, Rodrigo; Pereira, Gabriel Kalil Rocha
Abstract: Purpose: To evaluate the substrate masking ability of different ceramic systems used for complete crowns and assess the influence of their association with an opaque resin-based luting agent (OLA). Methods: Eleven ceramic groups were tested (n = 10). Bilayer groups were: ZrPc — zirconia + porcelain; CAD-onHT — zirconia + high translucent lithium disilitace; CAD-onLT — zirconia + low translucent lithium disilicate; LDPc — high opaque lithium disilicate + porcelain. Monolithic groups were: TZ — high translucent zirconia; TLS — translucent, zirconia-reinforced lithium silicate; HTLS — high translucent, zirconia-reinforced lithium silicate; LTLD — low translucent lithium disilicate; HTLD — high translucent lithium disilitace; LGC — leucite-reinforced glass ceramic; FC — feldsphatic ceramic. The substrates adopted were resin composites shaded A1 (control), A3.5 and C4; coppery and silvery metals. Color differences (ΔE00 ) and translucency parameter (TP00 ) were assessed with the CIEDE2000 formula. ΔE00 was obtained assessing the ceramic influence only and in association with OLA. Results: Zirconia groups presented lower ΔE00 and TP00 . CAD-on structures associated to OLA led to the lower ΔE00 when tested over metals. ΔE00 for LDPc were similar to zirconia when associated to OLA. Monolithic groups presented significant higher ΔE00 and TP00 compared to bilayers, with ΔE00 below the acceptability threshold only when associated to OLA over substrate shade A3.5. Conclusions: Ceramic type and the white-opaque resin-based luting agent presented a significant effect on the substrate masking ability. All the discolored substrates tested are adequately masked with veneered zirconia or with LDPc (preferably associated to OLA). The CAD-on technique associated with OLA improved the masking ability over metallic substrates.